Hop tests and psychological PROs provide a demanding and clinician-friendly RTS assessment of patients after ACL reconstruction, a registry study - Ramana Piussi; Susanne Beischer; Roland Thomeé; Eric Hamrin Senorski (BMC, 2020)
Abstract Background There is growing interest in assessing psychological well-being in patients after anterior cruciate ligament (ACL) reconstruction. It is unknown whether an assessment of psychological outcome in addition to tests of muscle function can facilitate decisions on return to sport (RTS). Therefore, the aim of this study was to evaluate passing rates in different physical RTS test batteries, with and without the inclusion of psychological outcome measures 1 year after ACL reconstruction. Method In this cross-sectional cohort study a total of 320 patients (51% men) aged 18-65 years were included 1 year after ACL reconstruction. Passing rates on different muscle function (MF) test batteries (with results presented as Limb Symmetry Index (LSI)), consisting of knee extension and flexion strength tests, 3 hop tests, and 2 psychological patient-reported outcomes (PROs); Quality of Life subscale from the Knee injury and Osteoarthritis Outcome Score (KOOS QoL) and ACL Return to Sport after Injury (ACL-RSI), were evaluated 1 year after ACL reconstruction. Muscle function test batteries comprised: 2 MF tests (vertical hop and hop for distance; pass = 90% LSI); 2 MF tests and 2 PRO (pass = 90% LSI, 62.5 points on KOOS QoL and 76.6 points on ACL-RSI), 5 MF tests (2 strength and 3 hop tests, pass = 90% LSI), and 5 MF tests and 2 PRO (pass = 90% LSI, 62.5 points on KOOS QoL and 76.6 points on ACL-RSI). Results Passing rates in the different test batteries were 47% for 2 MF tests, 19% for 2 MF tests and 2 PROs, 29% for 5 MF tests and 13% for 5 MF tests and 2 PROs. The use of psychological PROs together with tests of muscle function gave the lowest passing rate (13%). There was a very strong correlation between passing 2 hop tests and 2 PROs and passing 5 MF tests (rφ = 0.41) as well as passing 5 MF tests and 2 PROs (rφ = 0.79). Conclusion The use of hop tests together with psychological PROs provides a clinician-friendly RTS test battery for assessment 1 year after ACL reconstruction as the passing rate was 19% when using 2 hop-tests combined with 2 PROs, compared with 29% when using 5 tests of MF requiring advanced testing equipment.